Application of ARIMA-Decomposition in Forecasting Coffee Exports in Indonesia - Nusrang, Muhammad; Fahmuddin, Muhammad; Hafid, Hardianti; Muthahharah, Isma (Department of Statistics ITS, 2025)
Cocoa is one of Indonesia's primary commodities, playing an important role in the national economy, particularly in the agricultural and export sectors. However, Indonesia's cocoa exports have shown a declining trend in recent years, caused by a reduction in cocoa production. Therefore, more accurate forecasting is needed to support effective decision-making and maintain the competitiveness of this commodity. This research aims to obtain forecasts for cocoa exports in Indonesia using the ARIMA-decomposition method. The data used is secondary data obtained from the Central Statistics Agency's publication website. The data used is monthly data from 2014-2024 using the ARIMA-decomposition method The cocoa export variable referred to in this research is the volume of cocoa exports in Indonesia per month. The research results show that there are two models obtained, namely the ARIMA (1,0,0) and ARIMA (0,0,1) models. The ARIMA model (0,0,1) is the best because it has a smaller RMSE value than the ARIMA model (1,0,0). With results of forecasting cocoa export values using the hybrid ARIMA-decomposition method, namely January 2024 is 90,756,803.63, February 2024 is 94,087,978.29, March 2024 is 100,169,842.39, April 2024 is 90,693,529.69, May 2024 is 93,809,122.09, June 2024 is 100,601,810.69, July 2024 is 99,660,519.59, August 2024 is 105,630,962.89, September